2021
DOI: 10.1002/iroh.202002048
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the effect of multiple stressors on ecological structure of littoral lake macroinvertebrates

Abstract: Morphological alteration of shorelines and eutrophication both affect the biological integrity of European lakes. These pressures, often acting simultaneously, are difficult to tease apart. In this study, we related the number of taxa with specific habitat preference to habitat complexity across lakes of varying nutrient state. Habitat complexity at morphologically altered shorelines was significantly lower than at unaltered sites across trophic categories. A generalised linear mixed‐effects model showed decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…While we found that biodiversity trends differed across countries, crustaceans, insects, and molluscs showed similar patterns, characterised by positive trends across most countries and invasion status (Supporting information). Inferring identified trends to dreissenid impacts can also be difficult, considering the magnitude of additional stressors and ecosystem complexities that can affect macroinvertebrate communities (Jurca et al 2021), especially as temporal trends of Cohen's D showed similar signals to relative abundances (%) of D. polymorpha .…”
Section: Discussionmentioning
confidence: 99%
“…While we found that biodiversity trends differed across countries, crustaceans, insects, and molluscs showed similar patterns, characterised by positive trends across most countries and invasion status (Supporting information). Inferring identified trends to dreissenid impacts can also be difficult, considering the magnitude of additional stressors and ecosystem complexities that can affect macroinvertebrate communities (Jurca et al 2021), especially as temporal trends of Cohen's D showed similar signals to relative abundances (%) of D. polymorpha .…”
Section: Discussionmentioning
confidence: 99%
“…Sediment deposition can significantly alter the composition of the bottom substrate, enriching it with organic matter. Jurca et al (2021) pointed out that there was an absence of species with specific mesohabitat preferences in eutrophic lakes, as there is a clear linkage of macrophyte presence and species richness with eutrophication. All these factors should be taken into consideration when sampling for benthic macroinvertebrates in littoral zones of lakes in order to be able to draw conclusions without the confounding effects.…”
Section: Discussionmentioning
confidence: 99%